DESCRIPCIÓN Y EVALUACIÓN ANATÓMICA DE LESIONES ÓSEAS CRÁNEO-MANDIBULARES EN CETÁCEOS ODONTOCETOS DEL MAR PERUANO - Montes I., David (2004)
A total of 308 skulls and 200 jaws from 20 species and one hybrid of odontocetes cetaceans from the Peruvian Ocean were revised for anatomical description and evaluation of bone lesions. They were grouped into 8 types, plus those at the dental alveoli and osteolitic lesions caused by the nematode Crassicauda sp. From the total bone samples, at least 31.2% showed one type of craneo-mandibular lesion whereas the bottle nosed dolphin (Tursiops truncatus) was the most affected. Dental alveoli lesions were found in 13.3% of the samples and bone lesions caused by Crassicauda sp. were in 17.3% of the skulls. The most frequent lesions were hyperostosis and osteolisis, followed by osteomyelitis, malformations and occipitoatlantoaxial ankylosed joints. Adult males showed higher frequency of bone and dental alveolar lesions and is suggested that the latter type of lesions could be associated with severe cases of osteomyelitis and osteolisis at the maxilar and mandibular level. The pterigoid bone was the most affected by the Crassicauda sp. nematode.